Kalalah in Islamic Jurisprudence: A Critical Analysis of the Contemporary Views - Ali, Hamid; Bashir, Aijaz (Journal of Islamic and Religious Studies, 2021)
The importance of Islamic Law of inheritance, also known as “’Ilm al Farā‘id”, can be measured by the aḥādīth in which the Prophet, (PBUH) commanded to learn it along with the Holy Qur’ān, as he described it “half of the knowledge”. One of the types of heirs mentioned in the Holy Qur’an is “Kalālah”, and this word has been mentioned twice in the Holy Qur’ān. What is the meaning of kalālah, who are they and what are the rules of their inheritance, etc., such questions have become the subject of debate in modern times, and various opinions have appeared in this regard. Among these views is the opinion of Javed Ahmed Al-Ghamdi, who presented his opinion by decorating it with some specific comments from Tafāsir that he calls “the primary sources of Tafsīr.” This article analyzes the opinion of Javed Ahmed Al-Ghamdi and its impact on the assets of inheritance. The result of this discussion was that the meaning of “kalālah” is nothing but stepsister and stepbrother, and also the opinion of Al-Ghamdi was stated as an abandoned word in primary sources of Tafsīr. By accepting this view, the distribution of shares would not be possible according to the Qur’ānic command.